A Novel Power Quality Monitor Placement in Transmission Systems Method Using Binary Teaching Learning-Based Optimization Algorithm Considering Monitoring Redundancy - Mohammadi , Mohammad (International Journal of Integrated Engineering, 2022)
This paper deals with optimal employment of power quality monitors (PQMs) in transmission networks on the basis of the idea of monitor reach area. The proposed model uses binary string, representing the state presence or absence of PQMs in each bus of the network. In the current article, the binary version of the teaching learning-based optimization algorithm (BTLBO) is used. It has the ability to enhance the search potential and provides a rapid and secure convergence rate in the optimization process. The concept of redundancy is considered in this study. The overall cost function is formulated to optimize the two indices. The first one is the index of monitoring overlap, and the second one is the index of sag severity. In the solutions that in them the objective function experiments the minimum value, and also yield a full reachable power network, the evaluating the redundancy gives the final optimal answer. With an excellent redundancy, the buses of the system faced with faults are monitored more times, on average. In the current research, DIGSILENT software is employed in short circuit analysis, whereas the BTLBO manages the optimization process. In the proposed algorithm, the IEEE 30 Bus transmission network is considered as a case study, and results are compared to similar investigations to clarify the impressiveness of the proposed algorithm.